Usage of Repetitive Methods to Improve Students' Understanding of Zakat Material in Grade 5 at UPTD SD Negeri 57 Parepare - Anugrah, Anugrah; Saleh, Muhammad; Khalik, Abd. (International Journal Labs, 2025)
This research was motivated by the low comprehension of Zakat Fitrah among fifth-grade students at UPTD SD Negeri 57 Parepare. Initial observations indicated that 70% struggled with core concepts, while only 20% could apply the knowledge practically, largely due to reliance on traditional lecture methods. The aim of this research was to improve students’ understanding of Zakat Fitrah through implementation of the Repetitive Method. Utilizing a Classroom Action Research (CAR) approach based on the Kurt Lewin model, this study employed a qualitative, interpretive method and was conducted in two cycles. Data were collected through observation (of teacher and student performance), comprehension tests, and analysis of learning artifacts. Data validation was carried out through triangulation to ensure the credibility of the findings. The results showed significant improvement in students’ understanding. The mastery learning rate increased dramatically from 30% in the pre-cycle phase to 70% at the end of Cycle I and reached 100% by the end of Cycle II. This improvement covered the cognitive (conceptual and procedural understanding), affective (internalization of philanthropic values and social awareness), and psychomotor (practical application skills) domains. Teacher performance also showed notable improvements in adaptive and reflective classroom management. The conclusion of this study affirms that the Repetitive Method is effective in facilitating holistic understanding, active participation, and independent learning among students on the Zakat Fitrah material. This method successfully transformed rote learning into deep, applicable meaning-making, in line with constructivist and contextual learning principles